Précis of The Appearance of Ignorance: Knowledge, Skepticism, and Context, Vol. 2 - DeRose, Keith (International journal for the study of skepticism, 2020)
The Appearance of Ignorance develops and champions contextualist solutions to the puzzles of skeptical hypotheses and of lotteries. It is argued that, at least by ordinary standards for knowledge, we do know that skeptical hypotheses are false, and that we've lost the lottery. Accounting for how it is that we know that skeptical hypotheses are false and why it seems that we don't know that they're false tells us a lot, both about what knowledge is and how knowledge attributions work. Along the way, the following are all explained and defended: Moorean methodological approaches to skepticism, on which one seeks to defeat, rather than refute, the skeptic; contextualist responses to skepticism; contextualist substantive Mooreanism; the basic safety approach to knowledge and the double-safety picture of what knowledge is; insensitivity accounts of various appearances of ignorance; the closure principle for knowledge; and the claim that our knowledge that we are not brains in vats is a priori, despite its being knowledge of a deeply contingent fact.